Dinamika Kesenian Gandrung di Banyuwangi 1950-2013 - Raharjo, Bahagio (Humanis; Volume 15. No.2. Mei 2016, 2016)
T his research aimed to explain Gandrung tradisional dance by the historical perspective. To see the dynamic of Gandrung traditional dance from its growth and changes on it. How was Gandrung connect with the society around, ( including on its social, cultural, economic, politic, and religion ), which has been given a great influence and new challenges, it is also have role and give much impact to its society. All of these point are the subject of this research. The explanations of this research divided into three main period, that is orde lama (old regime), orde baru (new regime), and pasca reformasi (post-reform). This divided are based on the situation and requirement of these three periods. Every period have its own conditions, which have been given influence to Gandrung dance growth in Banyuwangi.
Keywords: Gandrung Dance, Banyuwangi, Dance Transition